2015
DOI: 10.1097/olq.0000000000000221
|View full text |Cite
|
Sign up to set email alerts
|

Could Home Sexually Transmitted Infection Specimen Collection With e-Prescription Be a Cost-Effective Strategy for Clinical Trials and Clinical Care?

Abstract: Background Results of a recent demonstration project evaluating feasibility, acceptability, and cost of a web-based STI testing and e-prescription treatment program (eSTI) suggest that this approach could be a feasible alternative to clinic based testing and treatment, but the results need to be confirmed by a randomized comparative effectiveness trial. Methods We modeled a decision tree comparing: 1) cost of eSTI screening using a home collection kit and an e-prescription for uncomplicated treatment versus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 10 publications
0
21
0
Order By: Relevance
“…If both uptake and case finding increase, expansion of STI services through sample self-collection may be cost-effective, though more research on this is warranted. Several studies have suggested that internet-based screening or other models using self-collection of samples for STI testing may be cost-effective compared with clinician-collected samples 27 54. Self-collection as an additional approach to STI testing and diagnosis supports the WHO global health sector strategy on STIs, which emphasises the need for identifying targeted accessible interventions, which ensure that people use the quality health services they need without suffering financial hardship or stigmatisation 53.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…If both uptake and case finding increase, expansion of STI services through sample self-collection may be cost-effective, though more research on this is warranted. Several studies have suggested that internet-based screening or other models using self-collection of samples for STI testing may be cost-effective compared with clinician-collected samples 27 54. Self-collection as an additional approach to STI testing and diagnosis supports the WHO global health sector strategy on STIs, which emphasises the need for identifying targeted accessible interventions, which ensure that people use the quality health services they need without suffering financial hardship or stigmatisation 53.…”
Section: Discussionmentioning
confidence: 99%
“…Because this study was designed to inform WHO guidelines on the viability of self-sampling as an additional means to increase testing, articles that compared self-collection of samples by the location of intervention delivery (ie, self-collection at home vs self-collection at the clinic) were not included. These articles have been reviewed elsewhere 19 26–31…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although this is a valid frustration, it is important for YMSM to understand the potential health consequences of untreated STIs. Given evidence of the feasibility and acceptability of home-based STI testing and treatment (Blake et al, 2015), future research could explore options to expedite treatment in the context of an eHealth study for YMSM.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the use of self samples to test for sexually transmitted infections among women in the US was more costly than clinic testing but also more effective at detecting infections (chlamydia, gonorrhoea, trichomonas), making the cost per diagnosis potentially lower. 17 Modelling showed that after screening validity and medical costs averted were taken into account, self sampling was less costly and clinically superior to clinic based sampling for chlamydia. 18 …”
Section: Costs and Efficiencymentioning
confidence: 99%